2006
DOI: 10.1111/j.1460-9568.2005.04547.x
|View full text |Cite
|
Sign up to set email alerts
|

Motor learning changes GABAergic terminals on spinal motoneurons in normal rats

Abstract: The role of spinal cord plasticity in motor learning is largely unknown. This study explored the effects of H-reflex operant conditioning, a simple model of motor learning, on GABAergic input to spinal motoneurons in rats. Soleus motoneurons were labeled by retrograde transport of a fluorescent tracer and GABAergic terminals on them were identified by glutamic acid decarboxylase (GAD)67 immunoreactivity. Three groups were studied: (i) rats in which down-conditioning had reduced the H-reflex (successful HRdown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
97
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(104 citation statements)
references
References 102 publications
(143 reference statements)
5
97
1
1
Order By: Relevance
“…All procedures complied with the Guide for the Care and Use of Laboratory Animals (National Academies Press, Washington, DC, 2011) and had been approved by the Institutional Animal Care and Use Committee of the Wadsworth Center. The procedures for electrode implantation, H-reflex monitoring, SMC stimulation, motoneuron labeling, and immunohistochemical processing have been described previously (Chen et al 2007a;Pillai et al 2008;Wang et al 2006aWang et al , 2009 and are summarized here. GABA receptor labeling methods are described in detail.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All procedures complied with the Guide for the Care and Use of Laboratory Animals (National Academies Press, Washington, DC, 2011) and had been approved by the Institutional Animal Care and Use Committee of the Wadsworth Center. The procedures for electrode implantation, H-reflex monitoring, SMC stimulation, motoneuron labeling, and immunohistochemical processing have been described previously (Chen et al 2007a;Pillai et al 2008;Wang et al 2006aWang et al , 2009 and are summarized here. GABA receptor labeling methods are described in detail.…”
Section: Methodsmentioning
confidence: 99%
“…While much remains to be learned about this hierarchy and the sites and mechanisms of plasticity, it is clear that SMC activity modifies the H-reflex by producing changes in the motoneuron (e.g., in firing threshold), as well as elsewhere in the spinal cord. Recent studies showing that operantly conditioned H-reflex decreases are accompanied by marked changes in GABAergic interneurons in the ventral horn and in GABAergic terminals on spinal motoneurons suggest that changes in GABAergic function may play a key role in producing the motoneuron plasticity directly underlying H-reflex conditioning (Wang et al 2006a(Wang et al , 2009.Another recent study revealed that weak electrical stimulation of SMC, like the operant conditioning protocol, can change (i.e., increase) H-reflex size (Chen et al 2007a). Motivated by this finding and by the data suggesting that change in GABAergic function contributes to H-reflex conditioning, the present study asked three questions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The enhanced oligosynaptic transmission to motoneurons that probably occurs with up-conditioning does not seem to be matched by a comparable reduction of oligosynaptic transmission after down-conditioning . Down-conditioning induces an increase in the number, size, and glutamic acid decarboxylase immunostaining of GABAergic terminals on motoneurons in down-conditioned rats (Wang et al 2004(Wang et al , 2006. Opposite changes are not seen in upconditioned rats (Wang et al 2004).…”
Section: Different Mechanisms For Up-and Down-conditioningmentioning
confidence: 99%
“…Although some of this plasticity appears responsible for the mode-appropriate H-reflex change (BelhajSaif and Cheney 2000;Carp and Wolpaw 1994;Curt et al 2002;Feng-Chen and Wolpaw 1996;Pillai et al 2004;Raineteau and Schwab 2001;Wang et al 2006;Wolpaw 1987), the rest of it may ensure the preservation of older behaviors or may simply reflect reactive downstream effects caused by changes in activity associated with plasticity elsewhere (Carp and Wolpaw 1995;Chen et al 2005a,b;Wang et al 2004;Wolpaw and Lee 1989). The plasticity responsible for the paradoxical H-reflex increase seen in Fig.…”
Section: Hrdown Conditioning In Csmc Ratsmentioning
confidence: 99%